PANTHEISTIC NARRATIVE EXPERIENCE: (IN THE WORLD OF ZOO STORIES BY VLADIMIR MARTINOVSKI) (Journal of Contemporary Philology, 2020)
Traditional and contemporary narratological examinations have underlined the vitality and primordial nature of narration as a key point for proper understanding of almost all human phenomena. Philology as a science puts the focus of its study primarily on human creatures and their ability to narrate. However, recent analyses provoke questions about other phenomena in nature (regarding humans, animals, plants etc.), especially because they all possess a unique life span and life stories. In that sense, the impressive workZoo Stories by Vladimir Martinovski represents a kind of cultural revolution in the Macedonian literature, re-examining the presupposed nature of human narration and its attributes. These stories represent the zoosphere as a specific chronotope, i.e. a platform where all the current categories of human postmodern culture are being revalorized. This kind of story construction, originating from the animals and dedicated to them, enables their transformation into active authors and undermines the metaphisically defined Cartesian subject (which overshadowed the role of natural diversity regarding human essence and existence). Hence, to write the story of “the Other“ underlines the necessity to see oneself as other, or to overcome the simple difference in favour of the spatial and temporal relations (considering the notion “différance” by Jaques Derrida).
Keywords: narration; animal story; Macedonian literature; Vladimir Martinovski; postmodern short story